A CADAVERIC STUDY OF THE AXILLARY ARTERY. - HUMBERTO FERREIRA ARQUEZ, (International Journal of Pharma and Bio Sciences, 2015)
The axillary artery is classically divided into three parts by pectoralis minor muscle and usually described as giving off six major branches. Anatomical variations in the branching pattern of axillary artery include: subscapular, lateral thoracic and the circumflex humeral. A total of 13 cadavers (26 embalmed axillae) were used for the study. In 92,4 % of the cases the axillary artery having a classic pattern of branching and in 7,6% of the cases the axillary artery showed variations in pattern of branching: First part did not give any branch, the second part gave off only three branches: lateral thoracic, thoracoacromialand large common trunk which later gave off thoracodorsal, circumflex scapular, subscapular, posterior circumflex humeral. The third part gave off only anterior circumflex humeral. Vascular variations in the axillary artery should be considered seriously as will implicate risk of bleeding during surgery also the difficulty in interpretation of the angiography.